A conversation with Jean Annan – Author of 7 Dimensions: Children’s Emotional Well-being (Kairaranga, 2023)
Dr Jean Annan’s 7 Dimensions: Children’s Emotional Well-being reflects the multiple perspectives she has encountered on children’s development through her broad experience with young people. She has worked as an educational psychologist, university lecturer, researcher, teacher, leader and systems facilitator in educational settings. In recent times, Dr Annan has supported school staff to integrate positive psychological practices into their everyday school programmes. This facilitation has focused on the integration of pro-active, nurturing practices designed for all children as well as the establishment of additional support for those young people who are in most urgent need. 7 Dimensions: Children’s Emotional Well-being builds on Dr Annan’s diverse publications in professional journals and books, the underlying theme of which has been the notion that if complex situations are rendered meaningful, they are easier to manage and positively redirect.In the video, Jean engages in conversation with Roger Phillipson. Roger is a registered psychologist and counsellor with the Ministry of Education in Tāmaki Makaurau. He has a passion for supporting the complex and layered lives of children with a focus on their wellbeing.